Rynek pośredników nieruchomości i jego dysfunkcje - Skiba, Ludwik (Real Estate Market and its Disfunctions, 2009)
The paper presents the role of real estate market in Poland, particularly the role of real estate agencies. The agencies' market has got quasi-monopolistic character.(original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 1, s. 835-839